Adult body size, sexual history and adolescent sexual development, may predict risk of developing prostate cancer: Results from the New South Wales Lifestyle and Evaluation of Risk Study (CLEAR). Issue 3 (26th October 2016) - Nair‐Shalliker, Visalini; Yap, Sarsha; Nunez, Carlos; Egger, Sam; Rodger, Jennifer; Patel, Manish I; O'Connell, Dianne L; Sitas, Freddy; Armstrong, Bruce K; Smith, David P
Abstract : Prostate cancer (PC) is the most common non‐cutaneous cancer in men worldwide. The relationships between PC and possible risk factors for PC cases ( n = 1, 181) and male controls ( n = 875) from the New South Wales (NSW) Cancer, Lifestyle and Evaluation of Risk Study (CLEAR) were examined in this study. The associations between PC risk and paternal history of PC, body mass index (BMI), medical conditions, sexual behaviour, balding pattern and puberty, after adjusting for age, income, region of birth, place of residence, and PSA testing, were examined. Adjusted risk of PC was higher for men with a paternal history of PC (OR = 2.31; 95%CI: 1.70–3.14), personal history of prostatitis (OR = 2.30; 95%CI: 1.44–3.70), benign prostatic hyperplasia (OR = 2.29; 95%CI: 1.79–2.93), being overweight (vs. normal; OR = 1.24; 95%CI: 0.99–1.55) or obese (vs. normal; OR = 1.44; 95%CI: 1.09–1.89), having reported more than seven sexual partners in a lifetime (vs. < 3 partners; OR = 2.00; 95%CI: 1.49–2.68), and having reported more than 5 orgasms a month prior to PC diagnosis (vs. ≤3 orgasms; OR = 1.59; 95%CI: 1.18–2.15). PC risk was lower for men whose timing of puberty was later than their peers (vs. same as peers; OR = 0.75; 95%CI: 0.59–0.97), and a smaller risk reduction of was observed in men whose timing of puberty was earlier than their peers (vs. same as peers; OR = 0.85; 95%CI: 0.61–1.17). No associations were found between PC risk and vertex balding, erectile function, acne, circumcision, vasectomy, asthma or diabetes. These results support a role for adult body size, sexual activity, and adolescent sexual development in PC development. Abstract : What's new? Many risk factors have individual associations with prostate cancer including age, obesity and family history. Here the authors formally examined the independent and interactive effects of a range of risk factors in the development of prostate cancer. The findings support a role for indicators of adult body size, sexual activity, and adolescent sexual development, supporting the concept that risk determinants early in life can influence prostate cancer development later on.